Cardiovascular Diseases and Type D Personality: Systematic Review and Meta-Analysis of the Literature of the Last 10 Years - Omar Anwar Saleh Al Nakhebi; Raluka Albu-Kalinovic; Adela Bosun; Oana Neda-Stepan; Marius Gliga; Cătălina-Angela Crișan; Ileana Marinescu; Cristian Mornoș; Virgil-Radu Enatescu (Life)
Background: Cardiovascular diseases (CVDs) are a leading cause of death globally, with a significant impact on public health and quality of life. In addition to traditional risk factors such as hypertension, diabetes, smoking, and hypercholesterolemia, a growing body of scientific evidence suggests the crucial role of psychosocial factors, including personality, in the development and prognosis of CVDs. In recent decades, researchers have focused on the so-called “type D personality.” Methods: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a literature search was conducted using the PubMed/Medline, Scopus, and Cochrane databases. Fifteen studies were included in the final quantitative analysis, involving 5687 people. The qualitative assessment of the studies included in this meta-analysis was conducted adopting the Quality System Tool. Results: Several studies have shown a significant correlation between type D personality and an increased risk of CVDs, as well as a worse prognosis in patients with established CVDs. The overall quality of the studies included in this synthesis ranged from 0.70 to 0.96, indicating the general good quality levels of the studies (69%). The association between type D personality and CVDs in terms of prevalence underlined a raw proportion of 0.36. Conclusions: This study reinforces the significance of type D personality as a psychological risk factor for CVD, with implications for both disease prevalence and severity.